Association of rs662799 variant and APOA5 gene haplotypes with metabolic syndrome and its components: a meta-analysis in North Africa. Issue 8 (13th August 2020) - Hechmi, Meriem; Dallali, Hamza; Gharbi, Meriem; Jmel, Haifa; Fassatoui, Meriem; Ben Halima, Yossra; Bahri, Sonia; Bahlous, Afaf; Abid, Abdelmajid; Jamoussi, Henda; Barakat, Abdelhamid; Kefi, Rym
Abstract: Apolipoprotein A5 ( APOA5 ) has been linked to metabolic syndrome (MetS) in several populations. In North Africa, only the Tunisian and Moroccan populations were investigated. Our aim is to assess the association between APOA5 gene variant (rs662799) and haplotypes with MetS in Tunisian population and to perform a meta-analysis in North Africa. A total of 594 Tunisian participants were genotyped for polymorphism rs662799 using KASPar technology. Two polymorphisms rs3135506 and rs651821 in APOA5 gene genotyped in our previous study, were used in addition to rs662799 to assess the haplotype association with MetS. The genotype of 875 participants was used for the meta-analysis. Statistical analyses were performed with R software. The rs662799 increases the risk of MetS under the dominant ( P =0.018) and the additive models ( P =0.028) in the Tunisian population. After stratification of the cohort following the sex and the geographic origin, a positive association of rs662799 with MetS was found for participant from the Northern region and for the women group. Only the haplotype AGT showed a significant association with MetS by decreasing the risk of the disease. The meta-analysis reported a significant association of rs662799 and rs3135506 with MetS. Our results showed a significant association between the APOA5 gene variants rs662799 and haplotypes with MetS and its traits in Tunisia. An impact of the sex and the geographic origin on the genotype distribution was highlighted. Our funding emphasizes the role of APOA5 in the development of MetS in North Africa.